Implementasi Aplikasi Pengelolaan Arsip Berbasis Web (Studi Kasus: Ruangan PUSLIA pada BAPENDA Sumatera Selatan) - Ilham, Muhammad; Dwi Jaya, Irfan; Purwani, Fenny (Universitas Multi Data Palembang, 2024)
The collection of data plays a crucial role as a source of information and a supervisory tool essential for an organization to carry out various tasks, such as planning, data analysis, development, policy formulation, and decision-making. Ineffectiveness in its management can have a negative impact on the image and reputation of the organization or institution. An example of this can be observed in the management of incoming and outgoing documentations. The Document Archive Information System is developed using the waterfall approach, with the Personal Hypertext Preprocessor (PHP) programming language. Visual Studio Code serves as the editor in the design process, while MySQL is integrated as the database system. The expectation is that this system will make a positive contribution to improving the quality of services provided by the Regional Revenue Office of South Sumatra Province to the public.